The role of creative self-efficacy and intrinsic motivation in delighting customers: The mediating role of positive psychological capital - Fouzia Hadi Ali; Aban Abid Qazi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
Delighting customers is attracting considerable attention of researchers from aruond the globe. So, the current study examines frontline employees' perceptions to perform delightful services by highlighting the effect of creative self-efficacy and intrinsic motivation through the intervention of positive psychological capital. Simple random sampling technique was applied to choose the sample. The data was gathered from different service-related brands working across Punjab, Pakistan. Partial Least Square Structural Equation Modeling (PLS-SEM) was used to test the model. The findings of this study assert that both creative self-efficacy and intrinsic motivation have a direct and indirect impact on employees' behavior to perform delightful services. The outcome of the study has significant theoretical and practical contributions.
Keywords: 330; frontline employees; creative self-efficacy; intrinsic motivation; positive psychological capital; delightful services